Histological and histochemical structure of sinus gland and neurosecretory granules in local freshwater Astacus Potamon magnum magnum (Pretzman)( arthropoda:Crustacea:Decapoda) - Baida Abdulaziz Barwari; Najem Shlemoon (College of Education for Pure Sciences, 2009)
Abstract The current study is the first one, at least, in Mosul University, and perhaps, in other universities in Iraq, being a new topic, the sinus gland. Furthermore, an original and successful method was found and used to overcome an old and difficult problem regarding the sectioning of the eyestalks which are covered by a thick, hard and calcified cuticle that causes destruction of the sections. Five histological and nine histochemical staining techniques were employed. The results have clearly shown the presence of only one sinus gland in each eyestalk. It is an elongated ellipsoid structure, dorsoventral in position and composed of four principal elements, the capsule, axon terminals, stromal tissues, and blood sinuses and vessels. Four patterns of neurosecretory granules were distinguished and classified according to certain basic criteria.